E-Book with a Scientific Approach on Natural Science Lesson for Fifth Grade Students of Elementary School - Putu Netha Kusumayuni; Anak Agung Gede Agung (Jurnal Ilmiah Sekolah Dasar, 2021)
Less innovative learning media and conventional methods impact students' interest and understanding of science lesson content. The purpose of this research was to describe the design process and know the results of E-Book validation according to the effects of expert reviews,  individual tests, and small group tests of scientifically designed  E-Book products. The products developed were expected to be utilized independently by students. This research was development research using model ADDIE development. The method of data collection in this study was a questionnaire with quantitative descriptive analysis techniques. This research was limited to the development stage, as it was impossible to involve many students during the  Covid-19pandemic. Media validation based on expert assessment of the lesson's content obtained a score of 91.67% with excellent qualifications, instructional design experts with a score of 100% with excellent qualifications, learning media experts received a score of 100% with excellent qualifications. Through individual tests on three students, user test results scored 93.33% with excellent qualifications, and user tests through small group tests on 12 students scored 95.00% with excellent qualifications. Based on the analysis of data from the validation results obtained, it can be concluded that this scientifically designed  E-Book media was eligible to be used as a learning medium on science lesson content in class V of Elementary School. The implications of the development of this scientifically based E-book required supporting facilities for the operation of  E-Book both laptops and mobile phones and supported by the ability to operate it to be used independently.